Carotid artery intima-media thickness in patients with acute ischemic stroke and its correlation with risk factors for atherosclerosis and/or stroke - Das, Shovan Kumar; Sarkar, Amit; Pramanik, Subhraprakash; Bandyopadhyay, Mitabha; Mondal, Koushik; Singh, Sanjai Kumar (Asian Journal of Medical Sciences, 2014)
Introduction: Stroke is the second leading cause of mortality worldwide. Ischemic stroke is more prevalent than hemorrhagic stroke and atherosclerosis is the major cause of ischemic stroke. The increased carotid artery intima-media thickness (CIMT) is considered to be useful indicator of early atherosclerosis. So, this study was aimed to correlate the relationship between atherosclerotic risk factors and intima-media thickness of carotid artery in patients with acute ischemic stroke. Material and Methods: In this cross-sectional study, 100 consecutive patients of acute ischemic stroke and 50 healthy relatives of patients as control were studied for presence of atherosclerotic risk factors and carotid artery intima?media thickness by B-mode Doppler ultrasonography. Results: In this age and sex matched study, higher CIMT measurement was found among patients of acute ischemic stroke than healthy controls (0.849 ± 0.196 vs 0.602 ± 0.092; p < 0.001). The CIMT was well correlated with smoking (Beta = 0.295; t = 5.728; 95% CI 0.088 to 0.181; p < 0.001); hypertension (Beta = 0.387; t = 6.518; CI 0.112 to 0.209; p < 0.001); di abetes (Beta = 0.237; t = 4.848; CI 0.074 to 0.175; p < 0.001); hypercholesterolemia (Beta = 0.292; t = 5.840; CI 0.096 to 0.195; p < 0.001), but not with age (p = 0.153). The CIMT was also found to be higher among acute ischemic stroke patients who were smoker, hypertensive, diabetic and hypercholesterolemic than non?smoker, normotensive, non-diabetic and normo-cholesterolemic respectively. Conclusion: The CIMT being indicator of atherosclerosis can be used as future predictor of ischemic stroke. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10301 Asian Journal of Medical Sciences Vol.6(1) 2015 22-27